Pengaruh Promosi dan Minat Beli Terhadap Keputusan Pembelian dengan Kepercayaan Pelanggan Sebagai Variabel Intervening Pada Sunmoracoffe - Haris Arsyad; Vicky Brama Kumbara; Della Asmaria Putri (CV. ITTC INDONESIA, 2026)
This study aims to determine the extent of the influence of promotion and purchase interest on purchasing decisions with customer trust as an intervening variable at Sunmoracoffe. The research method used is Structural Equation Modeling (SEM) with Partial Least Squares (PLS) 4.0, using a questionnaire with 100 respondents. The results of data analysis show that there is a positive and significant effect of promotion on customer trust. There is a positive and significant effect of purchase intention on customer trust. There is a positive and significant effect of promotion on purchasing decisions. There is a positive and significant effect of purchase intention on purchasing decisions. There is a positive and significant effect of customer trust on purchasing decisions. There is a positive and significant effect of the promotion variable on the purchasing decision variable through the customer trust variable as an intervening variable. The effect of promotion on purchasing decisions and the effect of purchase interest on customer decisions at Sunmoracoffe.